2017
DOI: 10.1177/1753193417739519
|View full text |Cite
|
Sign up to set email alerts
|

Radial styloidectomy for scaphoid nonunion advanced collapse – relevance of nonunion location

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…They underwent arthroscopic radial styloidectomy, which was useful in reducing radial wrist pain caused by SNAC [ 31 ]. However, radial styloidectomy of more than 3–4 mm might cause iatrogenic ligament injuries and carpal instability [ 32 , 33 ]. Recently, a cadaver study has shown that resection of more than 6 mm was associated with damage to radiocarpal ligaments [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They underwent arthroscopic radial styloidectomy, which was useful in reducing radial wrist pain caused by SNAC [ 31 ]. However, radial styloidectomy of more than 3–4 mm might cause iatrogenic ligament injuries and carpal instability [ 32 , 33 ]. Recently, a cadaver study has shown that resection of more than 6 mm was associated with damage to radiocarpal ligaments [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to our results, proximal scaphoid nonunion was associated with a higher mean score of global cartilage damage than waist or distal scaphoid nonunion. Another study also found that SNAC wrists with proximal scaphoid nonunion will probably have more chondral wear at the radial styloid and are more likely to require salvage procedures (Vutescu et al., 2018). Proximal scaphoid nonunion more likely allows dorsiflexion of the lunate if it is unrestrained by the distal scaphoid fragment, leading to dorsal intercalated segment instability.…”
Section: Discussionmentioning
confidence: 99%
“…When degenerative changes start, pain is caused by wear of articular cartilage rather than nonunion, so it is standard to perform salvage or arthroplasty surgery instead of an osteosynthesis procedure. Although for the first stage pain can be improved by resection of the radial styloid process and osteosynthesis of the scaphoid (Mayfield et al., 2019), in the second and third stages there are degenerative changes in the mid-carpal joint, so even if the osteosynthesis is successful, the pain may remain (Luchetti, 2018; Vutescu et al., 2018). Therefore, it is important to determine whether the arthritis has progressed to Stage 2 or not.…”
Section: Introductionmentioning
confidence: 99%
“…But, according to the study by Vutescu et al, radial styloidectomy should be performed with caution in cases with proximal pole scaphoid nonunion. Their results showed removal of part of the degenerated radial styloid could endanger the carpal extrinsic ligaments and cause carpal instability [ 33 ].…”
Section: Discussionmentioning
confidence: 99%